Effects of aging on word position encoding in Chinese reading - Zhiwei Liu; Yan Li; Jingxin Wang (BMC Psychology)
Abstract Recent research has highlighted a growing interest in word position coding during sentence reading, with young adults demonstrating flexible encoding of word positions. However, normal aging is associated with the visual and cognitive changes, which may impact this flexibility – particularly in Chinese reading, where word boundaries are not explicitly marked. This study examined age-related differences in the flexibility of word position encoding by investigating the transposed-word effect in young and older adults. Participants read sentences containing transposed words and control sentences while performing a rapid grammaticality decision task. Both age groups exhibited the transposed-word effect, with longer response times and higher error rates in the transposed-word condition compared to the control condition, indicating that the flexibility of word position coding is preserved across adulthood. Crucially, young adults showed a more pronounced transposed-word effect than older adults, suggesting an age-related reduction in the flexibility of word position coding. These findings suggest that while the flexibility of word position coding is preserved across adulthood, older adults display reduced flexibility compared to young adults in Chinese reading.